New Keynesianism and Aggregate Economic Activity - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 1997)
This paper addresses various attempts by so-called new Keynesians, writing mainly in the 1980s and 1990s, to strengthen the analytical basis, in particular the microeconomic foundations, of these assertions. What, exactly, have then the new Keynesians accomplished, and how should their contributions be valued in the relation to other recent contributions to macroeconomics?
Keywords: B22; B31; E12; 330; Economic Theory; Macroeconomics